UJI KELAYAKAN MODUL BERBASIS SELF HELP BOOK TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII SMPN 1 CIRACAP - Sa'diah, Humaeroh; Eti Rohaeti, Euis; Rezza Septian, Muhammad (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of this study was to determine the results of the validation of the feasibility of the self-help book-based module on learning motivation. Technical analysis of data using Microsoft Excel which is then analyzed descriptively. Instruments in the self-help book-based module validation assessment include the suitability of the material, the suitability of the design, instructions for use of the self-help book-based module and the benefits of the self-help book-based module to students. The results showed that the results of the self-help book-based module feasibility test conducted by 3 validators stated that the self-help book-based module was in the "very feasible" category with the results of the evaluation of material experts 95%, media experts 95.31%, and experts practitioners 95.45%. Subjects in this study amounted to 6 students for the limited test, and the broad test 24 students. The results of the assessment for the limited test obtained a score of 96.66% with the self-help book-based module product category very feasible to use, the wider test results obtained an assessment score of 85.54% which was in the very suitable category for use. Based on the results of expert assessments, and limited tests along with the extent of the feasibility test of the self-help book-based module on student learning motivation, it was declared feasible to be used by class VIII students of SMPN 1 Ciracap.